Exploring the secondary level teachers’ appointment system in Bangladesh for ensuring quality teachers - Mia, Mohammad Mamun; Islam, Muhammad Monirul; Rabbi, Md. Fajlay (Journal of Research in Instructional, 2023)
The study aims to investigate the issues embedded in the secondary-level teacher recruitment system from the structural perspective, which affect the motivation of the teaching profession, appointment and retention, and teacher development. The study applied the qualitative method and identified the issues that cause skill teacher shortage through causal relation analysis. The study used interviews with policymakers and administrators to identify the causes of the shortage of high-quality teachers in secondary institutions and discerned the solutions to ensure quality secondary education in Bangladesh. Adverse appointment and retention systems; and weak and stagnant teacher development facilities, were identified as the demotivating factors for taking the teaching profession. The solutions were found to enhance the attraction for teaching: firstly, by increasing salary, upholding teachers’ position in society and educational administration, and improving the working environment. The appointment and retention systems should be friendly by selecting and facilitating quality teachers. Lastly, a comprehensive and interconnected teacher development system should be initiated to ensure high-quality teachers at the secondary level.